Strategic analysis of the visual cattle identification market - Jost, Kyler (Kansas State University, 2023)
Cattle identification, specifically ear tagging, is crucial to our nation’s cattle producers and their practices aimed at ensuring the food safety and traceability throughout our meat supply. There is a disproportionately large body of research, scholarly articles and journal publications on EID/RFID tags, however, the research on visual ID is underdeveloped. The overarching purpose of this thesis is to develop a market analysis of cattle identification, which will serve as a basis and inform the process of developing a marketing strategy for Allflex visual ID tags including go-to-market strategy and implementation. The ultimate objective is to generate research insights aimed at informing the marketing strategies of Allflex brand of cattle identification products in the retail market in order to grow its presence within ag-retail sector, at both the dealer and the fleet store segments. The research involves external and internal analysis to identify key opportunities, threats, strengths and weaknesses as Merck Animal Health attempts to enter this segment as the only combined-offering company. The external analysis is the more extensive portion of the report which discusses major change forces and market drivers. Two main methods used for external analysis are the Porters Five Forces and STEEP analysis. The internal analysis focuses on resources examined by type (e.g. intangible resources, tangible resources, and human resources) and capabilities examined by functional areas (e.g. sales and marketing, supply management and demand planning, etc.). Findings are synthesized into specific actionable insights highlighting (i) resources and capabilities that are/can be sources of competitive advantage (temporary or sustainable), (ii) potential future scenarios based on the balance of strength, weaknesses, opportunities, and threats, (iii) direction of potential strategy, and (iii) a list of key strategic issues to serve as a basis for the formulation of marketing strategy.
Keywords: Ear tags; Cattle identification; Visual ID; Livestock identification; Merck Animal Health; Herd management